Facial Features Influence the Categorization of Female Sexual Orientation. (October 2013) - Tskhay, Konstantin O; Feriozzo, Melissa M; Rule, Nicholas O
Social categorization is a rapid and automatic process, and people rely on various facial cues to accurately categorize each other into social groups. Recently, studies have demonstrated that people integrate different cues to arrive at accurate impressions of others' sexual orientations. The amount of perceptual information available to perceivers could affect these categorizations, however. Here, we found that, as visual information decreased from full faces to internal facial features to just pairs of eyes, so did the accuracy of judging women's sexual orientation. Yet and still, accuracy remained significantly greater than chance across all conditions. More important, however, participants' response bias varied significantly depending on the facial feature judged. Perceivers were significantly more likely to consider that a target may be lesbian as they viewed less of the faces. Thus, although facial features may be continuously integrated in person construal, they can differentially affect how people see each other.